Data envelopment analysis approach to targeting in sustainable chemical process design: application to liquid fuels - Rodríguez-Vallejo,DF; Galán-Martín,Á; Guillén-Gosálbez,G; Chachuat,B (AIChE Journal, 2019)
This article presents a framework for combining data envelopment analysis with process systems engineering tools, aiming to improve the sustainability of chemical processes. Given a set of chemical processes, each characterized by performance indicators, the framework discriminates between efficient and inefficient processes in regard to these indicators. We develop an approach to quantifying the closest targets for an inefficient process to become efficient, while preventing unrealistic targets by accounting for thermodynamic limitations represented as mass and energy flow constraints. We demonstrate the capabilities of the framework by assessing a methanol production process with captured CO2 and fossil-based H2, in comparison to 10 alternatives. The methanol fuel is found to be suboptimal in comparison with other fuels. Making it competitive would require a significant (unrealistic in the short term) reduction in H2 price. Alternatively, the methanol fuel could become competitive upon combining fossil-based H2 with sustainably produced H2 via wind-powered electrolysis. © 2018 American Institute of Chemical Engineers AIChE J, 00: 000–000, 2018.